Early Supported Discharge for Neurorehabilitation Following Acquired Brain Injury - King, Regan; Seeger, Trevor; Wang, Meng; Li Pi Shan, Rodney; McGovern, Christine; Knox, Jason; Patel, Lisa; Fung, Tak; Sajobi, Tolulope; Debert, Chantel (Frontiers in Neurology, 2020)
Introduction: Early Supported Discharge (ESD) is a clinical flow management service offering interdisciplinary rehabilitation, wherein patients are provided supported in-home rehabilitation treatment; in comparison to conventional hospital-based rehabilitation model of service delivery. There has been little research into the functional outcomes for other types of acquired brain injury (ABI). Methods: In this prospective cohort study, ABI patients presenting at a level I trauma centre in Calgary, Canada were placed in either an ESD program or conventional inpatient rehabilitation (IPR) program based on their medical history and presentation. A small number of patients completed both programs (ESD+IPR group). ESD therapies were designed to emulate IPR. Participants completed professionally-rated Mayo-Portland Adaptability Index-4 (MPAI), Quality of Life after Brain Injury (QOLIBRI), Generalized Anxiety Questionnaire-7 (GAD7), Montreal Cognitive Assessment (MoCA), and Patient Health Questionnaire-9 (PHQ9) surveys at 1, 3, and 6 months following initial assessment pre-rehabilitation. Caregivers completed the Zarit Burden Interview (ZBI) at the same time points. The Supervision Rating Scale (SRS) and Disability Rating Scale (DRS) were completed at admission to rehabilitation and all follow-ups. Generalized estimate equations models were used to describe the three groups over time, including age as a covariate. Results: Significant effects of time were reported in the MPAI participant sub-score in the ESD and IPR groups (χ2(2)=42.429, p<0.000; χ2(2)=9.773,p=0.008), showing significantly higher scores between 1 than 3 month timepoints for both groups. ZBI scores were significantly lower in the ESD group at 1 month compared to 3 and 6 months (χ2(2)=31.252, p<.001). The proportion of patients with medical complications during rehabilitation was 25.3% in ESD compared to 74.7% patients in IPR. Conclusions: Improvements in functional outcomes were evident in patients participating in ESD and IPR, with more medical complications reported in the IPR group. Caregiver burden lessened over time in the ESD group but not in the IPR group. Both ESD and ESD+IPR groups can be considered viable alternatives to traditional inpatient rehabilitation. A randomized control trial would be required to properly compare rehabilitation streams. Further investigation into affective and lifestyle elements of ABI recovery would also improve our understanding of targeted neurorehabilitation in this population.